Histological analysis of biocompatibility of ionomer cements with an acid-base reaction - Rogério Lacerda dos Santos; Mirella de Fátima Liberato de Moura; Fabiola Galbiatti de Carvalho; Gymenna Maria Tenório Guênes; Polliana Muniz Alves; Matheus Melo Pithon (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The purpose of this study was to evaluate the inflammatory and cure events of acid-based reactions using glass ionomer cement used for cementation of crowns, bridges, onlays and orthodontic bands implanted in subcutaneous tissue, at different time intervals. A total of 48 male Wistar rats were used, distributed into 4 groups (n = 12), as follows: Group C (control, polyethylene), Group ME (Meron), Group KC (Ketac Cem) and Group PR (Precedent). The animals were sacrificed after time intervals of 7, 15 and 30 days, and their tissues were analyzed under an optical microscope for such events as inflammatory infiltrate, edema, necrosis, granulation tissue, multinucleated giant cells, young fibroblasts and collagen. The results was assessed using Kruskal-Wallis and Dunn's tests (p < 0.05). In the initial period, intense inflammatory infiltrate was observed for all the materials with no significant difference among them (p = 0.104). Groups PR and KC showed significant difference in relation to Group C, at 7 days (p = 0.025) and 15 days (p = 0.006). Edema and giant cells were more expressive in Group ME, differing significantly from Groups C (p = 0.023) and KC (p = 0.039), respectively, at 7 days. Group ME showed a statistically significant difference in relation to Groups PR and KC for the presence of young fibroblasts (p = 0.009) and for collagen (p = 0.002), at 7 days. Within the limits of this in vivo study, Precedent and Ketac Cem glass ionomer cements showed better tissue healing with a greater number of fibroblasts and collagen, as compared to Meron.